PRIMA-1MET cytotoxic effect correlates with p53 protein reduction in TP53-mutated chronic lymphocytic leukemia cells. (February 2020) - Jaskova, Zuzana; Pavlova, Sarka; Malcikova, Jitka; Brychtova, Yvona; Trbusek, Martin
Highlights: PRIMA-1 MET is effective in both TP53 -mutated and TP53 -wt CLL cells. PRIMA-1 MET induces apoptosis of TP53 -mutated CLL cells irrespective of baseline p53 level. Sensitivity of TP53 -mutated CLL cells to PRIMA-1 MET correlates with p53 reduction. Abstract: TP53 gene defects represent the most unfavorable prognostic factor in chronic lymphocytic leukemia (CLL). Although recently introduced small-molecule B-cell receptor signalling inhibitors have revolutionized CLL treatment, data for ibrutinib still point to impaired prognosis for TP53 -affected patients. Among cancer-associated TP53 mutations, missense substitutions predominate and typically result in a high mutated-p53 protein level. Therefore, rescuing the p53 tumor suppressor function through specific small molecules restoring p53 wild-type (wt) conformation represents an attractive therapeutic strategy for cancer patients with TP53 missense mutations. We tested the effect of mutated-p53 reactivating molecule PRIMA-1 MET in 62 clinical CLL samples characterized for TP53 mutations and p53 protein level. At the subtle PRIMA-1 MET concentrations (1–4 μM), most samples manifested concentration-dependent viability decrease and, conversely, apoptosis induction, with the response being similar in both the TP53 -mutated and TP53 -wt groups, as well as in the TP53 -mutated samples with p53 protein stabilization and without it. PRIMA-1 MET was able to reduce mutated p53 protein in a proportion of TP53 -mutated CLL samples, and this reduction correlated with a significantly stronger viability decrease and apoptosis induction than samples with stable p53 levels. CLL cells are mostly sensitive to PRIMA-1 MET apart from those with stable mutated p53.